Pengaruh Efisiensi Pengelolaan Aset, Return On Equity dan Struktur Modal terhadap Pertumbuhan Ekuitas pada Perusahaan PT. Ciputra Development Tbk. - Rudi Sanjaya; Dini Hasanah M; Mohamad Gilang Surpiyana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the effect of asset management efficiency, Return on Equity (ROE), and capital structure on equity growth at PT. Ciputra Development Tbk. Equity growth is an important indicator in assessing a company's ability to increase shareholder value sustainably. This study uses a quantitative approach with a case study method at PT. Ciputra Development Tbk. The data used are secondary data in the form of the company's financial statements for the period 2012-2023. The independent variables include the efficiency of Total Asset Turnover, ROE, and Debt To Equity Ratio, while the dependent variable is equity growth. Data analysis was carried out using multiple linear regression to test the relationship between the independent variables and the dependent variables, Hypothesis Testing, t-test and F-test